Identifikasi parasit darah pada ayam buras di Pasar Inpres Naikoten Kota Kupang - Edwin Prasetyo Salut; Julianty Almet; Aji Winarso (Jurnal Veteriner Nusantara, 2019)
Important blood parasites in chickens are members of the phylum Apicomplexa, which are Haemoproteus, Leucocytozoon and Plasmodium. Blood parasite can cause low productivity and death in poultry farms. This study aimed to identify and determine the prevalence of blood parasites infection in poultry in Naikoten traditional market, Kupang city. The sampling technique was purposive sampling. One hundred and fifty domestic poultry blood samples have been selected by purposive sampling, collected in Ethylene Diamine Tetra Acetat (EDTA) tube and then taken to the Laboratory of Parasitology to be made into blood smears which were then examined using a 100x of microscope magnification. Blood parasites that had been identified are Plasmodium sp., And Haemoproteus sp. From one hundred and fifty samples, 62 chickens were positively infected by Plasmodium sp., 26 chickens were infected by Haemoproteus sp., The prevalence of infection of Plasmodium sp., 41.3%, Haemoproteus sp., 17.3%, and the prevalence of mixed infections of both parasites was 2.03%.